NT1014, a novel biguanide, inhibits ovarian cancer growth in vitro and in vivo. Issue 1 (December 2016) - Zhang, Lu; Han, Jianjun; Jackson, Amanda; Clark, Leslie; Kilgore, Joshua; Guo, Hui; Livingston, Nick; Batchelor, Kenneth; Yin, Yajie; Gilliam, Timothy; Gehrig, Paola; Sheng, Xiugui; et al.
Abstract Background NT1014 is a novel biguanide and AMPK activator with a high affinity for the organic cation-specific transporters, OCT1 and OCT3. We sought to determine the anti-tumorigenic effects of NT1014 in human ovarian cancer cell lines as well as in a genetically engineered mouse model of high-grade serous ovarian cancer. Methods The effects of NT1014 and metformin on cell proliferation were assessed by MTT assay using the human ovarian cancer cell lines, SKOV3 and IGROV1, as well as in primary cultures. In addition, the impact of NT1014 on cell cycle progression, apoptosis, cellular stress, adhesion, invasion, glycolysis, and AMPK activation/mTOR pathway inhibition was also explored. The effects of NT1014 treatment in vivo was evaluated using the K18 − gT121+/− ; p53fl/fl ; Brca1fl/fl (KpB) mouse model of high-grade serous ovarian cancer. Results NT1014 significantly inhibited cell proliferation in both ovarian cancer cell lines as well as in primary cultures. In addition, NT1014 activated AMPK, inhibited downstream targets of the mTOR pathway, induced G1 cell cycle arrest/apoptosis/cellular stress, altered glycolysis, and reduced invasion/adhesion. Similar to its anti-tumorigenic effects in vitro, NT1014 decreased ovarian cancer growth in the KpB mouse model of ovarian cancer. NT1014 appeared to be more potent than metformin in both our in vitro and in vivo studies. Conclusions NT1014 inhibited ovarian cancer cell growth in vitro and in vivo, with greater efficacy than the traditional biguanide, metformin. These results support further development of NT1014 as a useful therapeutic approach for the treatment of ovarian cancer.